Inpatient multidisciplinary care can prevent deterioration of renal function in patients with chronic kidney disease: a nationwide cohort study - Abe, Masanori; Hatta, Tsuguru; Imamura, Yoshihiko; Sakurada, Tsutomu; Kaname, Shinya (Frontiers in Endocrinology, 2023)
Background: Multidisciplinary care is necessary to prevent worsening renal function and all-cause mortality in patients with chronic kidney disease (CKD) but has mostly been investigated in the outpatient setting. In this study, we evaluated the outcome of multidisciplinary care for CKD according to whether it was provided in an outpatient or inpatient setting. Methods: This nationwide, multicenter, retrospective, observational study included 2954 Japanese patients with CKD stage 3–5 who received multidisciplinary care in 2015–2019. Patients were divided into two groups: an inpatient group and an outpatient group, according to the delivery of multidisciplinary care. The primary composite endpoint was the initiation of renal replacement therapy (RRT) and all-cause mortality, and the secondary endpoints were the annual decline in the estimated glomerular filtration rate (ΔeGFR) and the changes in proteinuria between the two groups. Results: Multidisciplinary care was provided on an inpatient basis in 59.7% and on an outpatient basis in 40.3%. The mean number of health professionals involved in multidisciplinary care was 4.5 in the inpatient group and 2.6 in the outpatient group (P < 0.0001). After adjustment for confounders, the hazard ratio of the primary composite endpoint was significantly lower in the inpatient group than in the outpatient group (0.74, 95% confidence interval 0.59–0.95, P = 0.018). In both groups, the mean annual ΔeGFR was significantly improved at 24 months after the initiation of multidisciplinary care. Conclusion: Multidisciplinary care may significantly slow deterioration of eGFR in patients with CKD and be more effective in terms of reducing initiation of RRT and all-cause mortality when provided on an inpatient basis.